ANALISIS HUBUNGAN MOTIVASI KERJA DENGAN KINERJA PEGAWAI PADA PERPUSTAKAAN PROVINSI JAMBI - Husama Husama (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2014)
This writing discusses the main problem, namely Work Motivation and Performance which is implemented in Jambi Province Library Board employees. This thesis aims to see and analyze the relationship between work motivation and employee performance at the Jambi Provincial Library. The research methodology used in this study is descriptive analysis, and in collecting data through literature, interviews and questionnaires. Based on this research, it is recommended that meeting the needs of maintenance motivation factors and the motivation factors given by the Jambi Provincial Library to its employees must be maintained and further improved. With the background of facts and reality, it can be concluded that employee motivation and employee performance are interconnected at the Jambi Provincial Library Board. It needs attention from the leadership of the Jambi Province Library Board in order to be able to provide motivation or encouragement to employees so they can work as expected by the organization in order to create a conducive work climate and progress in employee performance.